PENGARUH STUKTUR KEPEMILIKAN INSTITUSIONAL DAN FREE CASH FLOW TERHADAP KEBIJAKAN HUTANG DAN NILAI PERUSAHAAN - Ni Luh Ria Handayani (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2016)
The Importance of Debt Policy and Value Company became the basis for investors to invest in the company went public. The value of the company can be seen from the company's stock price, where the higher the stock price, the higher the value of the company. This study aims to determine the effect of ownership structure institutionally and Free Cash Flow to Debt Policy and Value Company. The population in this study were all consumer goods companies listed in Indonesia Stock Exchange in 2010-2013. Samples were taken 21 samples from the population by purposive sampling method with several criteria that must be met. The research data is secondary data obtained from the Indonesia Stock Exchange (www.idx.co.id) and ICMD 2010-2013. Testing hypotheses of the study used path analysis techniques. The results showed that: 1) Ownership institutionally positive and significant effect on the Debt Policy. 2) Ownership institutionally positive and significant impact on the Company's value. 3) Free Cash Flow positive and significant effect on the Debt Policy. 4) Free Cash Flow positive and significant effect on the value of the company. 5) Debt Policy and the positive effect is not significant to the Company's value.